Choosing the appropriate genetic processes for applying genetic algorithm to issues which has a linear association between chromosome genes (The issue of enhancement the performance signalized Intersections) - غزال, بديع; بلسم عيد (Latakia University Journal -Engineering Sciences Series, 2022)
Genetic algorithm is considered as one of artificial intelligence fields which use evolution and the theory of natural selection, it is an effective tool for solving optimization problems. The integration of (GA) parameters is vital to the success of the (GA). These parameters include mutation and crossover rates as well as populations that are important issues in GA, in addition to the correct choose of genetic processes. This paper discusses the construction of a genetic algorithm that is restricted by conditions on generating chromosomes and applying genetic processes, to improve the delay time of vehicles that pass the "four-armed" signalized Intersections in the Syrian governorates, where the genetic algorithm is used to control and optimize the time distribution of the total traffic light cycle duration of the traffic intersection. In order to achieve the least possible time delay for vehicles crossing it. the chromosome is represented by five genes, the first of which is the total traffic light cycle duration of the traffic intersection, and the remaining four genes represent the percentage of the green time period of the cycle for each arm of the intersection, which Linearly related to each other, chromosomes are evaluated by a fitness function, which determines their fitness for transmission it to the next generation compared to other chromosomes. The fitness function was chosen to be a mathematical model that expresses the total delay time on the intersection [1], Since the chromosome associated with the shortest time in a generation is the optimal solution within this generation, the effect of the generation size and the effect of genetic processes (crossover, mutation) on applying of the genetic algorithm in solving this issue has been studied to reach the least possible delay time.